Change Detection Analysis and Deforestation Rates in Oluwa Forest Reserve, Ondo State, Nigeria - J.O. Mephors; O.S. Afolabi; O.M. Ogoliegbune; I.S. Adamu; A.R. Orunkoyi (Journal of Applied Sciences and Environmental Management)
Land use and land cover (LULC) intensified by the conversion of natural resources for food purpose, urbanization, and other socioeconomic benefits as affected forest reserves and made them undergo rapid, wide-ranging changes. This study examined the use of GIS and remote sensing techniques to gain a quantitative understanding of the spatiotemporal dynamics of LULC. Maximum likelihood classifier approach was used to detect LULC changes in the study area of 1989 to 2019 using three Landsat images from 1989, 2004 and 2019. The observed changes were indicative of a decrease in the expanse of the forested area of (1989 to 2004), with 1989 having (89.2%) and 2004 (74.1%) with a differential range loss of (-15.1%), and a differential annual rates of deforestation of (-1.236436715). During the following 15 years (2004 to 2019) the annual rate of deforestation has increased to (1.303364215) with year 2019 recording (90.1%). The overall annual deforestation rate in the forested area of the studied period (1989-2019) is 0.033464, which implies that there is a percentage gain in forest. It is observed in this study that the highest deforestation rate was registered between 1989 and 2004. Non-forest occupied 10.8% in 1989 increasing in year 2004 by25.9% with a positive annual rate of change (5.831312231) and negative annual rate of change (-6.411388077) between 2004 to 2019, meaning there was loss in nonforest cover. The overall annual deforestation rate in the non - forested area of the studied period (1989-2019) is -0.29004. According to this evolution, the annual rate of deforestation was estimated to be (0.033464%) for the three defined periods in the forested area. So therefore to avoid drivers leading to changes in land use land cover stressing the complexity that is related to sustainable management of protected areas, urgent action is necessary to reduce loss of biodiversity due to deforestation and land degradation.